2017
DOI: 10.1177/1059601117750532
|View full text |Cite
|
Sign up to set email alerts
|

Teaming Up or Down? A Multisource Study on the Role of Team Identification and Learning in the Team Diversity–Performance Link

Abstract: Prior literature paints an incoherent picture on the relationship between team diversity and performance. The current article investigates circumstances under which demographic diversity (gender and nationality) facilitates performance. Based on the categorization-elaboration model, we build a theoretical framework to demonstrate the crucial role of team learning and efficacy as mediators, and team identification as a moderator to understand how and when demographic diversity facilitates team performance. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 68 publications
(147 reference statements)
0
16
0
4
Order By: Relevance
“…This research attempts to shed light on the ambiguous findings reported in prior literature for the team diversity and performance relationship (Van Veelen and Ufkes, 2019). We provide an insight into the factors by which team diversity can foster a positive team performance.…”
Section: Discussionmentioning
confidence: 94%
“…This research attempts to shed light on the ambiguous findings reported in prior literature for the team diversity and performance relationship (Van Veelen and Ufkes, 2019). We provide an insight into the factors by which team diversity can foster a positive team performance.…”
Section: Discussionmentioning
confidence: 94%
“…Confronted with turbulent circumstances, organizations become increasingly dependent on teams to carry out creative work to maintain the flexibility and sustained competitive advantages ( Horwitz and Horwitz, 2007 ; Kearney et al, 2009 ; Hoever et al, 2012 ; Van Dijk et al, 2012 ; Van Veelen and Ufkes, 2019 ). Despite the recognition of the importance of team creativity, which is defined as the generation of novel and useful ideas regarding products, processes, and procedures ( Amabile, 1996 ; Shin and Zhou, 2007 ), the conditions that foster team creativity require further investigation ( Shalley et al, 2004 ; Shin and Zhou, 2007 ; Hoever et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Para lidar com inovações tecnológicas e mercados globalizados, o trabalho tem sido cada vez mais organizado em equipes de projeto, especialmente em organizações de Tecnologia da Informação (TI). Isto porque a estruturação por projetos possibilita maior adaptabilidade ao ambiente de trabalho complexo e à execução de tarefas dinâmicas (Veelen & Ufkes, 2019).…”
Section: Introductionunclassified
“…Nas organizações de TI, a aprendizagem de equipes tem sido crescentemente investigada (Edmondson, 1999;Kandukuri & Nasina, 2017;Harvey, Bresman, Edmondson, & Pisano, 2020) porque ela gera capacidade de resposta organizacional à mudança e vantagens em longo prazo (Edmondson, 2002). Por exemplo, existem evidências de que a aprendizagem da equipe diminui o custo de implementação de mudanças, aumenta a velocidade de entrega de produtos, a eficácia de processos operacionais (Akgün, Lynn, Keskin, & Dogan, 2014) e o desempenho da equipe (Veelen & Ufkes, 2019;Wiese & Burke, 2019). Nas equipes de projeto, a aprendizagem gera maior agilidade na identificação de problemas e soluções, bem como auxilia na redução dos custos de planejamento, projeto e implementação (Kandukuri & Nasina, 2017).…”
Section: Introductionunclassified